Less State, More Internet - Silveira, Juelinton; Paranaiba, Adriano; Arantes, Elaine (MISES: Interdisciplinary Journal of Philosophy, Law and Economics, 2023)
This work studies the impact of state intervention on the development of telecommunications companies in Brazil and digital inclusion in areas with low population density. The research was developed to answer the following question: How did state intervention influence the development of telecommunications companies in Brazil and digital inclusion in areas with low population density? The specific objectives of this work are: 1. Demonstrate the Austrian theory of interventionism and exemplify its practice in the telecommunications industry; 2. Present and analyze secondary data from the telecommunications industry that help understand the impact caused by interventionism in this area or the benefits of its lack of small providers; 3. Understand and conclude whether the lack of interventionism in small internet providers in sparsely populated areas brought benefits to this industry. This is a theoretical-empirical article based on bibliographical research in light of the Austrian Theory of Interventionism, following the case study strategy and applied in the context of small Brazilian operators in the telecommunications sector. The results pointed to an acceleration of the development of these operators when there were fronts of bureaucracy and deregulation that affected the small providers.